Towards a Tangible Pedagogy: Dimensions of Tactility at the Bauhaus (Revista Apotheke, 2025)
In the epistemic context of a fundamental skepticism towards the existing knowledge system, the Bauhaus school was in pursuit of “unlearning”: dismissing conventional learning and promoting pre- linguistic, intuitive approaches- which also led to adoptions of non-academic modes of perception and included an interest in pre-modern knowledge systems.
Keywords: Bauhaus; pedagogy; tactility; haptic; optics